Secondary school science pupils' rankings of science and technology related global problems : a comparison of the responses of rural-Northern Sotho, urban-Xhosa and urban-English speaking pupils in South Africa to meeting basic needs in the context of the 1994 Government White Paper on Reconstruction and Development - Le Grange, Lesley Lionel Leonard (Centre for Educational Research, 2016)
Bibliography: pages 66-71.